2010
DOI: 10.1038/nmat2785
|View full text |Cite
|
Sign up to set email alerts
|

Robust isothermal electric control of exchange bias at room temperature

Abstract: Voltage-controlled spin electronics is crucial for continued progress in information technology. It aims at reduced power consumption, increased integration density and enhanced functionality where non-volatile memory is combined with highspeed logical processing. Promising spintronic device concepts use the electric control of interface and surface magnetization. From the combination of magnetometry, spin-polarized photoemission spectroscopy, symmetry arguments and first-principles calculations, we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
567
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(606 citation statements)
references
References 38 publications
34
567
4
1
Order By: Relevance
“…Demonstrating electrical control of coercivity 19,24 , exchange bias 25,26 or magnetic anisotropy 20,27 is insufficient because, respectively, an electrically addressable coercivity is inextricably linked with an applied magnetic field; because exchange bias is an interfacial phenomenon that cannot readily drive magnetization reversal throughout a film of significant thickness; and because no new magnetic anisotropy axis can lie more than 901 from the anisotropy axis along which the local magnetization initially lies. It has been suggested that this latter challenge may be overcome by applying a suitable sequence of normal stresses near the pre-existing magnetic anisotropy axes of a small homogeneously magnetized Stoner-Wohlfarth particle 28,29 , but this has not been experimentally realised.…”
Section: Between Ferroelectricmentioning
confidence: 99%
“…Demonstrating electrical control of coercivity 19,24 , exchange bias 25,26 or magnetic anisotropy 20,27 is insufficient because, respectively, an electrically addressable coercivity is inextricably linked with an applied magnetic field; because exchange bias is an interfacial phenomenon that cannot readily drive magnetization reversal throughout a film of significant thickness; and because no new magnetic anisotropy axis can lie more than 901 from the anisotropy axis along which the local magnetization initially lies. It has been suggested that this latter challenge may be overcome by applying a suitable sequence of normal stresses near the pre-existing magnetic anisotropy axes of a small homogeneously magnetized Stoner-Wohlfarth particle 28,29 , but this has not been experimentally realised.…”
Section: Between Ferroelectricmentioning
confidence: 99%
“…This boundary polarization, roughness insensitive, has been demonstrated to contribute to the magnetization. 27,28 Accordingly, the hysteresis loops included in Fig. 4 can be associated with these two main contributions; one responsible for the large magnetization values due to the ferrimagnetic (FiM) magnetite nanoparticles, which superimposes the antiferromagnetic contribution responsible for the subtle slope and almost non-saturation of the magnetization at high field values that corresponds to the chromium oxide magnetic phase identified.…”
Section: View Article Onlinementioning
confidence: 99%
“…For spintronic device applications growing similar films on Cr 2 O 3 (0001) would offer several important advantages compared to other oxides because of its magnetoelectric properties 5,10 and the ability to produce a single magnetic domain via field cooling. 11 However, we find that C MBE on chromia yields only disordered graphite below ~ 800 K and the desorption of C above this temperature. In this paper, we use experiment and DFT to understand the origin of this dramatic difference between growth of graphene on Co 3 O 4 (111) compared to Cr 2 O 3 (0001) to provide insight into developing guidelines for obtaining cohesive graphene/oxide films.…”
mentioning
confidence: 62%